The role of key features in predator recognition by untrained birds - Beránková, Jana; Veselý, Petr; Sýkorová, Jana; Fuchs, Roman (Animal cognition, 2014)
The most important role in the recognition and categorization of predators (as well as other animals) is usually attributed to so-called key features. Under laboratory conditions, we tested the role of yellow eyes (specific for the genus Accipiter in European raptors) and hooked beak (common for all European birds of prey) in the recognition of the sparrowhawk (Accipiter nisus) by untrained great tits (Parus major) caught in the wild. Using wooden dummies, we interchanged either one of these potential key features or the body of the sparrowhawk (predator) and domestic pigeon (harmless bird). The tested tits showed three types of behaviour in the presence of the dummies: fear, interest without fear, and lack of interest. Eye interchange lowered fear of the sparrowhawk, but did not cause fear of the pigeon. Beak interchange did not lower fear of the sparrowhawk. Eye interchange caused increased interest in both species. Thus, a specific sparrowhawk feature is necessary for correct sparrowhawk dummy recognition but a general raptor feature is not. On the other hand, a specific sparrowhawk feature on a pigeon dummy is not enough to prompt sparrowhawk recognition. Thus, key features play an important, but not exclusive, role in predator recognition. An increased interest in some of the modified dummies implies that the tits have a general concept of a sparrowhawk. The individual variability in behaviour of tits is discussed.
Keywords: predátorské chování; rozpoznávání (psychologie); zpěvní ptáci; oči; Female; Predatory Behavior; Animals; Songbirds; ženské pohlaví; Columbidae; mužské pohlaví; Hawks; Male; Recognition, Psychology; některé rody čeledi Accipitridae; Eye; zvířata